Observation of CH⋅⋅⋅π Interactions between Methyl and Carbonyl Groups in Proteins. (22nd May 2017) - Perras, Frédéric A.; Marion, Dominique; Boisbouvier, Jérôme; Bryce, David L.; Plevin, Michael J.
Abstract: Protein structure and function is dependent on myriad noncovalent interactions. Direct detection and characterization of these weak interactions in large biomolecules, such as proteins, is experimentally challenging. Herein, we report the first observation and measurement of long‐range "through‐space" scalar couplings between methyl and backbone carbonyl groups in proteins. These J couplings are indicative of the presence of noncovalent C−H⋅⋅⋅π hydrogen‐bond‐like interactions involving the amide π network. Experimentally detected scalar couplings were corroborated by a natural bond orbital analysis, which revealed the orbital nature of the interaction and the origins of the through‐space J couplings. The experimental observation of this type of CH⋅⋅⋅π interaction adds a new dimension to the study of protein structure, function, and dynamics by NMR spectroscopy.